Application of Generative Artificial Intelligence Tool in Tourism in China - Su, Hongxia; Liu, Huifen; Sun, Shan; Xu, Mian (International Journal of Global Economics and Management, 2024)
With the rapid progress of artificial intelligence and natural language processing technology, large-scale language models such as ChatGPT are increasingly widely used in the tourism industry, profoundly changing the traditional mode of tourism services. This paper discusses the application of Generative AI tools in tourism and its challenges and risks from both the supply side and the demand side. The research points out that travel agencies are faced with the loss of tourists, technical threshold and cost pressure, and tourists also have certain risks when using Generative AI tools for travel planning and decision-making. In order to cope with these challenges and risks, this paper puts forward corresponding countermeasures and suggestions. Travel agencies should get committed to improving information quality, strengthening technical updates and ensuring information security. At the same time, tourists should also be vigilant when using Generative AI tools and plan their travel itinerary properly. These strategies help travel agencies and tourists better adapt to the changes brought by new technologies and promote the sustainable development of the tourism industry.